Russell body gastritis: case report Gastrite com corpúsculos de Russell: relato de caso - Eduardo Cambruzzi; Karla Lais Pêgas; Fernanda de Fátima Laus (Sociedade Brasileira de Patologia Clínica, 2012)
Russell body gastritis (RBG), which can be associated with Helicobacter pylori (HP) infection, is a recently acknowledged lesion characterized by the presence of eosinophilic intracytoplasmic inclusions in plasmacytes. Herein the authors discuss the morphological aspects of a case of RBG in a male patient with clinical complaint of epigastric pain. Upper endoscopy revealed areas of erythema/edema in the antrum. As far as microscopy is concerned, a mononuclear inflammatory infiltrate was identified on the lamina propria, with plasma cells containing Schiff acid periodic (PAS) positive eosinophilic intracytoplasmic globules, which showed positive immunostaining for CD79a, CD138, and kappa/lambda light chains. HP was identified by Giemsa stains. A gastrite com corpúsculos de Russell (RBG), que pode estar associada à infecção por Helicobacter pylori (HP), é uma lesão recentemente reconhecida que se caracteriza pela presença de inclusões eosinofílicas intracitoplasmáticas em plasmócitos. Neste relato, os autores discutem os aspectos morfológicos de um caso de RBG em um paciente masculino com queixa clínica de dor epigástrica. A endoscopia revelou áreas de eritema/edema no antro. À microscopia, um infiltrado inflamatório mononuclear foi identificado na lâmina própria, com plasmócitos exibindo glóbulos eosinofílicos intracitoplasmáticos ácido periódico de Schiff (PAS) positivos, que apresentaram imunoexpressão positiva para CD79a,CD138 e cadeias leves kappa/lambda. HP foi identificado na coloração de Giemsa.